INFLUENCE OF THE CATION NATURE ON SPECTRAL CHARACTERISTICS OF COBALT(II)-NICKEL(II) PHOSPHATES - Антрапцева, Надія; Філіпова, Поліна; Подобій, Олена; Біла, Галина (SWorldJournal, 2023)
The work was carried out with the aim of studying the influence of the cation nature on the spectral characteristics of cobalt(II)-nickel(II) hydrogenphosphates of the general formula Co1-хNiхHPO4·1.5H2O .Using the methods of Infrared and Raman